Influência de cultivares e densidades de plantas sobre a eficácia da proteção química no patossistema soja-phakopsora pachyrrizi - Domingues, Lucas da Silva (2010)
Aiming to evaluate the response of ten soybean cultivars subjected to three arrangements of plants and eight fungicide programs in terms of expression and the development of Asian rust, penetration of light on the canopy, productivity and yield components of soybean experiment was conducted during the 2008/2009 season, in Itaara / RS. In the field, cultivars FCep 55, BMX Apollo, BMX Titan, BRS 243, A 8000, CD 214, NK 70, BRS Pampa, FCep 59 and Monasca were subjected to densities off 160, 300 and 440 thousand plants ha-1 and eight programs fungicide management: P1- treatment control, P2 - epoxiconazole + pyraclostrobin with application to closing the row space and 21 days after the first application; P3 - epoxiconazole + pyraclostrobin application to closing the row space and 28 days; P4 - epoxiconazole + pyraclostrobin with application in R1 and 21 days; P5 - epoxiconazole + pyraclostrobin with applications closing the row space, 21 days after the first application and the third application 14 days after the second; P6 - tebuconazole + carbendazin with application in closing the row space and 21 days after the first application; P7 - tebuconazole + carbendazin application to close row space and 28 days after and P8 - tebuconazole + carbendazin with application in R1 and 21 days. The variables were: percentage of light penetration within the canopy, Area under the progress disease curve (AUPDC), grain yield and yield components. The experimental design was a randomized block, with 4 replications and three-way design (10 cultivars x 3 planting densities x 8 fungicide management programs). For percentage of light penetration in the canopy, BMX Apollo cultivar performed better with values close to 1% when subjected to higher density. For the variables AUPDC and productivity cultivars might be grouped as responsive, not responsive and unresponsive to reduce the plant population. The responsive cultivars for AUPDC were FCep55, BMX Apollo, BRS 243, CD 214, has had this behavior to yield the cultivars FCep 55, A 8000, BMX Titan, BRS 243 and NK 70. Management programs had the same trend for these two variables where the program with three applications of epoxiconazole + pyraclostrobin showed lower AUPDC value and higher yield. The number of branches per plant showed that all cultivars reduce the production of branches when exposed to high density, which resulted in condensing the grain on the main stem, especially the cultivar BMX Apollo that concentrated 99.84% of the grain on the main stem and the higher density was only 0.02 branches for plant. For the yield components number of pods for m2 and number of grains for pod was significant difference only for the cultivars and plant density. For densities, the higher density of plants resulted in reducing the number of pods for area, grains per pod, among the cultivars NK 70 showed the highest number of pods for m2 and the cultivar BMX Apollo largest number of grains for pod. The mass of 1000 grains was the variable with little variation among worked. There interaction between programs and cultivars, where the maturity cultivars achieved the largest masses. For the participation of thirds in the number of pods, there was only difference among cultivars where the variability of response between the cultivars shows that this variable has genetic domain.